Patterns of expressions of transforming growth factor and epidermal growth factor receptor in squamous cell lesions of the urinary bladder. Issue 8 (August 1998) - Tungekar, M F; Linehan, J
Abstract : AIM: To investigate the patterns of expression of transforming growth factor alpha (TGF-alpha) and epidermal growth factor receptor (EGFR) in squamous metaplasia and squamous cell carcinomas of the urinary bladder with and without schistosomiasis. METHODS: Immunohistochemical study of the expression of TGF-alpha and EGFR in squamous metaplasias (n = 12) and various grades of squamous cell carcinomas (n = 21) of the bladder with and without schistosomiasis. RESULTS: Focal cytoplasmic and membranous positivity for EGFR and TGF-alpha was seen in all cases of squamous metaplasia. The markers were diffusely coexpressed in a concordant pattern in areas of hyperplastic keratinising squamous metaplasia. A similar pattern of positivity was seen in verrucous carcinomas (n = 2) and well differentiated squamous carcinomas (n = 6). Progressive loss of differentiation was associated with increasing loss of EGFR staining while TGF-alpha staining was retained. Squamous cell carcinoma in situ (n = 2) showed focal positivity for TGF-alpha and EGFR. There were no differences in staining patterns between cases with and without schistosomiasis. CONCLUSIONS: The coexpression of TGF-alpha and EGFR by well differentiated squamous cell carcinomas and hyperplastic keratinising squamous metaplasia is consistent with the active regulatory role exerted by this autocrine loop. There is regional absence of expression of EGFR but not of TGF-alpha in squamous cell carcinomas of lesser differentiation, suggesting heterogeneity of such control in these tumours. The focal expression of the two markers in squamous cell carcinomas in situ indicates a possible second pathway of oncogenesis for less differentiated tumours. These observations may have important implications for the effectiveness of putative growth factor based treatments.